Fungal and Bacterial Communities in the Rhizosphere of Pinus tabulaeformis Related to the Restoration of Plantations and Natural Secondary Forests in the Loess Plateau, Northwest China. (25th December 2013) - Yu, Hong-Xia; Wang, Chun-Yan; Tang, Ming
Abstract : Chinese pine ( Pinus tabulaeformis Carr.) is widely planted for restoration in destroyed ecosystems of the Loess Plateau in China. Although soil microbial communities are important subsurface components of the terrestrial ecosystems, little is known about fungal and bacterial communities in the rhizosphere of planted and natural P. tabulaeformis forests in the region. In this study, fungal and bacterial communities in the rhizosphere of P. tabulaeformis were analyzed by nested PCR-DGGE (denaturing gradient gel electrophoresis). Diversity analysis revealed that the values of the Shannon-Wiener index (H ) and the Simpson index (D ) of fungal communities were higher in natural secondary forests than in plantations except for the 3-year-old site. Moreover, the values of species richness, H, and D of the bacterial communities were also higher in the former. Totally, 18 fungal and 19 bacterial DGGE band types were successfully retrieved and sequenced. The dominant fungi in the rhizosphere of P. tabulaeformis belonged to the phylum of Basidiomycota, while the dominant bacteria belonged to the phylum of Proteobacteria. Principal component analysis indicated that fungal and bacterial species were more unitary in plantations than in natural secondary forests, and the majority of them were more likely to appear in the latter. Correlation analysis showed no significant correlation between the fungal and bacterial community diversities.